Review: Optimal Shock and Vibration Isolation. (1998) - Balandin, D.V.; Bolotnik, N.N.; Pilkey, W.D.
Abstract : This is a review of the investigations into the field of optimum shock and vibration isolation, including the mathematical foundations of both optimal open-loop and optimal feedback isolation systems. This survey covers the literature from the initial studies to the present.